Sosialisasi Pencegahan Tindakan Bullying di Sekolah Dasar Negeri Margawangi - Muhamad Yusup Rachmat; Nurul Husnayain; Nida Nurul Hidayati; Yunia Mustika; Muhammad Helmi Alfian; Iqbal Fatardo (PT. ALHAFI BERKAH INDONESIA, 2024)
Human social life cannot be separated from interactions with each other. The development of social interactions will increase with age. Improvement in behavior in children is highly dependent on the family. The family has an important role in teaching how to behave well and correctly to their sons and daughters, but if the family environment is not involved in the social development of the individual, it will have a bad impact, one of which is bullying. This bullying is carried out by a person or a certain group to hurt someone physically or psychologically and make the victim traumatized and depressed. In this activity we try to participate in preventing bullying in students of Margawangi Elementary School. The Elementary School environment is an environment that is vulnerable to bullying. In this activity we conduct socialization and education for students to prevent bullying in schools.